2011
DOI: 10.1093/carcin/bgr034
|View full text |Cite
|
Sign up to set email alerts
|

Src activates HIF-1α not through direct phosphorylation of HIF-1α-specific prolyl-4 hydroxylase 2 but through activation of the NADPH oxidase/Rac pathway

Abstract: Hypoxia-Inducible Factor (HIF)-1α/β heterodimer is a master transcription factor for several genes involved in angiogenesis, glycolysis, pH balance and metastasis. These HIF-1 target genes help tumors to overcome forthcoming metabolic obstacles as they grow. Under normoxic condition, the HIF-1α subunit is hydroxylated by its specific prolyl-4 hydroxylase 2, given the acronym PHD2. Hydroxylated HIF-1α becomes a target for von Hippel-Lindau (VHL), which functions as an E3 ubiquitin ligase. Src prevents hydroxyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
36
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 43 publications
2
36
0
1
Order By: Relevance
“…Previous findings from our laboratory have indicated that LPA-Gαi2 signaling could rapidly stimulate Rac via p130Cas/Src dependent pathway [15]. It has also been shown that Src can stimulate an increase in the levels and subsequent activation of HIF1α involving Rac-stimulated ROS generation via NADPH oxidase [54]. Connecting these two independent observations, our data presented here points to a signaling paradigm in which the signaling by LPA propagates through Gαi2 and Src to HIF1α (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings from our laboratory have indicated that LPA-Gαi2 signaling could rapidly stimulate Rac via p130Cas/Src dependent pathway [15]. It has also been shown that Src can stimulate an increase in the levels and subsequent activation of HIF1α involving Rac-stimulated ROS generation via NADPH oxidase [54]. Connecting these two independent observations, our data presented here points to a signaling paradigm in which the signaling by LPA propagates through Gαi2 and Src to HIF1α (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al demonstrated that mechanical strain stimulation of ROS generation in glomerular mesangial cells is induced by Rac1 activation via an Src signaling pathway [13]. In response to other non-mechanical stimuli, Rac1 is also recognized as a downstream signaling molecule of Src signals [37][38][39][40][41]. In our study, pretreatment of cells with the Src inhibitor PP2 and shRNA targeted to Src blocked periodic mechanical stress-induced Rac1 phosphorylation and activation, which suggests that Src activation of Rac1 at Ser71 is responsible for the signaling transduction mechanisms in chondrocytes under conditions of cyclic mechanical stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence showed that c-Src activated NAPDH oxidase in VSMCs (Lassegue et al, 2012;Seshiah et al, 2002;Touyz et al, 2003). Furthermore, Lee et al (2011) demonstrated that c-Src activated HIF-1α through activation of the NADPH oxidase/Rac pathway. Thus, we investigated the effects of CGA on NADPH oxidase activity in hypoxic condition in PASMCs.…”
Section: Discussionmentioning
confidence: 99%